Design of a Microstrip Bandpass Filter with Open-Loop Resonator for Sub-6ghz 5G Applications - El Nashef, Georges Zakka; Coşkun, Ahmet Halit; İmeci, Şehabeddin Taha (Datateam Business Media Limited, 2026)
The rapid growth of wireless technology is calling for reliable and high performing communication systems. Filters play a crucial role here, enabling the selection of desired signals. The compact filter structures in particular are essential, which often require high dielectric constants to reduce their size. Thus, designing and developing efficient compact RF filters has become a crucial task.
Keywords: Bandpass Filters; Signal Processing; Communications Systems; Compact Filter; Desired Signal; Filter Structures; High Dielectric Constants; Microstrip Bandpass Filters; Open-Loop Resonators; Rapid Growth; RF Filters; Wireless Technologies